Coinware for Multilingual Passphrase Generation and Its Application for Chinese Language Password - Lee, Kok-wah; Ewe, Hong-tat (2006)
Civilian cryptosystem applies Kerckhoffs law to have security dependency 100% on the password secrecy. This reflects the fact that key length and key space are very important to ensure enough entropy or randomness for securing a cryptosystem. For stronger password, passphrase is suggested Currently, there are three methods to generate passphrase: Acronym, full sentence and diceware. Here, we propose an alternate method to diceware: Coinware, by using the coin. Coinware uses four coins to generate one hexadecimal digit. The created word lists will be in hexadecimal order and can be applied for multilingual passphrase generation. Its exemplary application for Chinese language password is shown. Readily-made Chinese character word list in the CJK unified ideographs of the Unicode enables fast hexadecimal reading for random passphrase generation. Hanyu Pinyin and Sijiao Haoma are used for Chinese character romanization to uniquely represent each Han character. Jyutping is then used for Cantonese language.